Workshop Etika Jurnalisme Warga di Era Digital Bagi Pelajar SMA dan Mahasiswa - Djamal, Muchamad Fauzi (Jurnal Pustaka Dianmas, 2022)
The current digital era and information disclosure make it easy to convey information through writing or video by disseminating it directly via the internet, especially social media. This convenience further strengthens citizen journalism, which has existed for a long time. However, citizen journalism must be accompanied by a responsibility to convey information correctly and accurately so that disinformation does not occur in society. Therefore, an understanding of ethics in disseminating information to the public must be owned when carrying out citizen journalism activities. Through training activities with the theme "Citizen Journalism in the Digital Era: Creative and Innovative," it is hoped to increase understanding of citizen journalism ethics, principles, and things that must be avoided in citizen journalism. The training is carried out through lecture methods, discussions and the practice of conducting citizen journalism activities.